Genomic and transcriptomic analysis unveils population evolution and development of pesticide resistance in fall armyworm Spodoptera frugiperda. Issue 7 (27th October 2020) - Gui, Furong; Lan, Tianming; Zhao, Yue; Guo, Wei; Dong, Yang; Fang, Dongming; Liu, Huan; Li, Haimeng; Wang, Hongli; Hao, Ruoshi; Cheng, Xiaofang; Li, Yahong; et al.
Abstract: The fall armyworm (FAW), Spodoptera frugiperda, is a destructive pest native to America and has recently become an invasive insect pest in China. Because of its rapid spread and great risks in China, understanding of FAW genetic background and pesticide resistance is urgent and essential to develop effective management strategies. Here, we assembled a chromosome-level genome of a male FAW (SFynMstLFR) and compared re-sequencing results of the populations from America, Africa, and China. Strain identification of 163 individuals collected from America, Africa and China showed that both C and R strains were found in the American populations, while only C strain was found in the Chinese and African populations. Moreover, population genomics analysis showed that populations from Africa and China have close relationship with significantly genetic differentiation from American populations. Taken together, FAWs invaded into China were most likely originated from Africa. Comparative genomics analysis displayed that the cytochrome p450 gene family is extremely expanded to 425 members in FAW, of which 283 genes are specific to FAW. Treatments of Chinese populations with twenty-three pesticides showed the variant patterns of transcriptome profiles, and several detoxification genes such as AOX, UGT and GST specially responded to the pesticides. These findings will be useful in developing effective strategies for management of FAW in China and other invaded areas.